Impacts of Heart Failure and Physical Performance on Long-Term Mortality in Old Patients With Chronic Kidney Disease - Weng, Shuo-Chun; Chen, Yu-Chi; Hsu, Chiann-Yi; Lin, Chu-Sheng; Tarng, Der-Cherng; Lin, Shih-Yi (Frontiers in Cardiovascular Medicine, 2021)
Objective: In patients with chronic kidney disease (CKD), physical functional limitations and heart failure (HF) are common, and each is associated with adverse outcomes. However, their joint effects on mortality are not clear. Design and Methods: Using administration data from the geriatric department in a tertiary hospital, retrospective longitudinal analyses of patients aged >=65 years with CKD were consecutively enrolled from February 2010 to November 2015. Baseline CKD stages, HF with reduced and preserved ejection fraction (HFrEF & HFpEF), Rockwood frailty index, handgrip strength (HGS), 6-meter walking speed, and timed up-and-go test were used to predict the prevalence of frailty, physical disability, and all-cause mortality. Results: Among 331 old patients with CKD, their mean age was 81.3 ± 6.6 years. CKD stages showed the following distributions: stage 3, 74.9%; stage 4, 15.7%; stage 5, 9.4%. The prevalence of HF was 23.3%, and Rockwood frailty was 74.3%. Rockwood frailty and HF were both significantly associated with CKD stages. After a mean follow-up period of 3.1 ± 2.1 years, 44 patients died, and a crude analysis showed that stage 4, stage 5 CKD, low HGS, and Rockwood frailty index were associated with mortality. Regarding the survival of these patients, the adjusted mortality hazard ratio for CKD stage 5 was 3.84 against stage 3A [95% confidence interval (CI) 1.51–9.75], 1.04 (95% CI 1.01–1.07) for higher Rockwood frailty score, 4.78 (95% CI 1.26–18.11) for HFrEF, and 3.47 (95% CI 1.15–10.42) for low HGS. Survival analysis using Kaplan-Meier survival plots showed that patients with both HF and poor HGS had the poorest survival. Conclusions: Our study showed that both low physical performance and HF were common in old CKD patients and were associated with CKD stages. HF, frailty, and HGS all independently predicted the mortality of these CKD patients. The mortality is especially high amongst individuals with both HF and decreased HGS.